Numerical analysis and investigation of classifier blade angle on classification efficiency in coal power plants - Raveen Lingam Ramalinggam (2023)
In this study, the processes of the coal pulverizer mainly the classification of coal is studied. The classifier in the coal pulverizer serves as a filter allowing finer coal particles to escape through it, while sending coarse particles back for regrinding. While many works have been conducted on the crusing of the coal particles less extensive research has been done on the classifier. Thus, in this study the effect of the classifier blade angle which is the steepness of the classifier on both the classification efficiency and the quality of classification is investigated. The initial hypothesis of this study indicates that by merely increasing the classifier blade angle, the classification efficiency of the model would also increase. This is because theoretically increasing the classifier blade angle would lead to an increase in the number of coal particles that escape out of the classifier. By using the same theory and principle, an increase in the number of coal particles escaping through the classifier would result in more coarse particles also escaping through it. This would in theory lead to a decrease in the quality of classification.